Business Climate Versus the Attraction of Direct Foreign Investments in Albania - Shoraj, Dritan; PhD Perparim Dervishi (European Journal of Multidisciplinary Studies, 2017)
There are statistics that foreign direct investments (FDI) in Albania have significantly declined. Business climate and skill of policies to attract FDI in Albania has apparently not impacted the promotion of investments from foreign businesses. This study assesses the business environment disadvantages and the readiness and availability of foreign investors to take risks with their investments in a foreign market facing the business climate of the host country, as well as the skill or failure of the latter for long term cooperation. Some basic components of the business climate in Albania, impact and their attractiveness to foreign investors will be analyzed and assessed. The research methodology selected for this study is the quantitative one, where a number of about 100 CEO and administrators of medium and big foreign companies in Albania have been planned to be interviewed. The measuring instrument will be standardized and after data collection, a series of analyses will be built such as correlation, means, standard deviations, frequencies, Chi-square (?2) where the value p00.5. Analysis of variables will be realized through SPSS program. The study will be closed with relevant conclusions and recommendations.